2002
DOI: 10.1182/blood-2002-03-0777
|View full text |Cite
|
Sign up to set email alerts
|

The impact of clonal evolution on response to imatinib mesylate (STI571) in accelerated phase CML

Abstract: In chronic myelogenous leukemia (CML), the development of chromosomal abnormalities in addition to the Philadelphia chromosome (clonal evolution) is considered by many to be a feature of accelerated phase (AP). Imatinib mesylate (STI571), a selective inhibitor of the Bcr-Abl tyrosine kinase, has significant activity in AP CML. As clonal evolution could allow Bcr-Abl independent proliferation, we analyzed its impact on the outcome of 71 AP patients treated with 600 mg of imatinib mesylate. Fifteen patients had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
86
0
5

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(99 citation statements)
references
References 18 publications
8
86
0
5
Order By: Relevance
“…The researchers concluded that good prognosis was still possible if cytogenetic clonal evolution was the only criterion of accelerated phase, whereas clonal evolution with other accelerated features predicted for the worst outcome. Our results confirm some of the findings of O'Dwyer et al 41 and provide additional insights with more detailed (multivariate) analysis of a larger number of patients (n ϭ 498 versus 71 patients) with a longer follow-up (median of 30 months versus mean of 11 months), and a comparison to patients with chronic-phase CML. Unlike the results of O'Dwyer et al, 41 our study did not identify clonal evolution to be associated with a significant difference in major or complete cytogenetic response rates within specific CML phases (ie, chronic Ϯ clonal evolution, accelerated Ϯ clonal evolution).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The researchers concluded that good prognosis was still possible if cytogenetic clonal evolution was the only criterion of accelerated phase, whereas clonal evolution with other accelerated features predicted for the worst outcome. Our results confirm some of the findings of O'Dwyer et al 41 and provide additional insights with more detailed (multivariate) analysis of a larger number of patients (n ϭ 498 versus 71 patients) with a longer follow-up (median of 30 months versus mean of 11 months), and a comparison to patients with chronic-phase CML. Unlike the results of O'Dwyer et al, 41 our study did not identify clonal evolution to be associated with a significant difference in major or complete cytogenetic response rates within specific CML phases (ie, chronic Ϯ clonal evolution, accelerated Ϯ clonal evolution).…”
Section: Discussionsupporting
confidence: 80%
“…Our results confirm some of the findings of O'Dwyer et al 41 and provide additional insights with more detailed (multivariate) analysis of a larger number of patients (n ϭ 498 versus 71 patients) with a longer follow-up (median of 30 months versus mean of 11 months), and a comparison to patients with chronic-phase CML. Unlike the results of O'Dwyer et al, 41 our study did not identify clonal evolution to be associated with a significant difference in major or complete cytogenetic response rates within specific CML phases (ie, chronic Ϯ clonal evolution, accelerated Ϯ clonal evolution). However, clonal evolution was still independently associated with worse survival in both chronic and accelerated phase, independent of other prognostic factors.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…20,21 However, in cases where accelerated phase is defined solely by clonal evolution, the outcome is heterogeneous and the rate of response to imatinib (with short follow-up) may to be similar to that of chronic phase. [22][23][24] The development of clonal cytogenetic abnormalities in Ph-negative cells has also been observed during imatinib treatment of CML. In the two largest studies, none of 55 patients with Ph-negative clonal abnormalities had clinical features of myelodysplasia.…”
Section: Introductionmentioning
confidence: 99%
“…5,7 Imatinib counteracts BCR-ABL tyrosine kinase and induces apoptosis in BCR-ABL-positive cells [8][9][10] in a caspase-dependent fashion. 11,12 Recently, however, it has been revealed that responses to imatinib are not necessarily remarkable or durable in some patients with BCR-ABL-positive leukemia, [13][14][15][16][17][18][19][20][21][22] and thus an increasing number of studies have searched for a novel therapy targeting the BCR-ABL-induced signaling pathways. 5 Cell death is generally classified into 2 categories, apoptosis 23,24 and necrosis.…”
Section: Introductionmentioning
confidence: 99%